2019
DOI: 10.1177/0260106019887890
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of dental caries by grape seed extract supplementation: A systematic review

Abstract: Background: Dental caries are the most prominent chronic disease of children and adults worldwide, and facilitating evidence-based, preventative care for their prevention is critical. Caries are traditionally and successfully prevented by regular fluoride use, but there are opportunities to halt and restore caries with alternative agents in addition to fluoride use. Grape seed extract (GSE) is a readily available plant-based supplement that, due to its concentrated levels of proanthocyanidins, has promising ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…In grape seeds the most concentrated class is flavanols, proanthocyanidins or condensed tannins, which have a strong antioxidant activity and have been studied for their important role in dental caries prevention. 21 Depending on the solvent used or on the method of extraction, lipids are more or less intensively extracted and it is known that oil has very moderate antiradical activity, as determined by DPPH radical scavenging, in contrast to the strong antiradical activity of polyphenols; but, overall, the lipid fraction is easily oxidizable, producing a radical which increases the oxidability of the substrate. 30 Most of the samples were judged as 'neither pleasant nor unpleasant'; this is probably due to the fact that, as expressed by many, the flavor of the extracts was masked by the mint flavor of the commercial toothpaste base.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In grape seeds the most concentrated class is flavanols, proanthocyanidins or condensed tannins, which have a strong antioxidant activity and have been studied for their important role in dental caries prevention. 21 Depending on the solvent used or on the method of extraction, lipids are more or less intensively extracted and it is known that oil has very moderate antiradical activity, as determined by DPPH radical scavenging, in contrast to the strong antiradical activity of polyphenols; but, overall, the lipid fraction is easily oxidizable, producing a radical which increases the oxidability of the substrate. 30 Most of the samples were judged as 'neither pleasant nor unpleasant'; this is probably due to the fact that, as expressed by many, the flavor of the extracts was masked by the mint flavor of the commercial toothpaste base.…”
Section: Resultsmentioning
confidence: 99%
“…16 The recovery of antioxidant compounds from grape pomace after the vinification process is a research activity that has developed in the last decade, and several applications in medicine have been carried out to control hyperglycemia in diabetic mice 17 or to control oxidative stress in obese mice, 18 to protect endothelial and muscle cells through an increase in glutathione (GSH) levels as potent scavengers of free radicals, 19 and providing protection against colon carcinogenesis. 20 For dental care a recent review by Delimont and Carlson 21 reported that grape seed extract properties facilitate dental caries prevention, by inhibiting proliferation of bacterial biofilms on tooth surfaces and promoting dental remineralization. 22 In this research, the general hypothesis has been whether the potential use of seed polyphenols, mainly tannins, extracted from grape pomace after the vinification process, in a commercial toothpaste formulation could enhance its antioxidant activity by maintaining stability at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, the remineralizing effect of GSE, of which an active ingredient is proanthocyanidin, has been noted in caries on the dentin surface or root caries. It has also been reported as effective in preventing caries formation (Delimont & Carlson, 2020; Silva, Goncalves, Borges, Bedran‐Russo, & Shinohara, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, grape seeds are mainly used for restorative dental work and prevention of dental caries. The main compound of grape seeds responsible for the beneficial actions in dental pathologies is represented by the proanthocyanidin group [112]. In vivo studies have shown that grape seed extract has the ability to reduce colonization of S. mutans, the main bacterium involved in tooth decay [113].…”
Section: Herbs As Therapeutic Agents In Dentistrymentioning
confidence: 99%
“…The mechanisms of action underlying this therapeutic property consist of: (i) grape seed extract mediates remineralization; (ii) grape seed extract prevents dental degradation and (iii) grape seed extract influences the dental tensile strength. These mechanisms are due to the ability of phytocompounds in grape extract to bind to enzymes responsible for tooth enamel degradation and to promote crosslinking of collagen-rich dentin surfaces [112].…”
Section: Herbs As Therapeutic Agents In Dentistrymentioning
confidence: 99%